Added-value porous materials for controlled thymol release obtained by supercritical CO2 impregnation process. Issue 5 (September 2019) - Milovanovic, Stoja; Markovic, Darka; Ivanovic, Jasna
This study explores utilization of biodegradable and biocompatible polymers for controlled release of natural bioactive substance. For that purpose, poly(ε-caprolactone) (PCL) beads, cellulose acetate (CA) film, and poly lactic- co -glycolic acid (PLGA) flakes were impregnated with thymol by employing environmentally friendly process of supercritical carbon dioxide (scCO2 ) impregnation. At selected pressure and temperature, prolongation of operating time increased thymol loading. Pure scCO2 did not affect CA film with average pore diameter of approximately 3 µm, while it enabled change of PCL beads and PLGA flakes into foams with average pore diameter approximately 175 µm and 87 µm, respectively. Additionally to scCO2, thymol acted as a plasticizer increasing pore size of polymers up to three times. Kinetic of thymol release from selected samples was tested using phosphate buffer saline at 37°C and successfully described with Korsmeyer–Peppas, zero-order, first-order, and Higuchi models. The suggested method of PCL, CA, and PLGA supercritical impregnation led to development of porous, solvent free, added-value materials that release thymol in a controlled manner from 5 h to several days.